Efectos de la estimulación eléctrica neuromuscular en pacientes con Incontinencia Urinaria. - Valencia Salinas, Lizeth Nataly (2023)
ABSTRACT: neuromuscular electrical stimulation is the functional technique in patients with inability to control urinary activity called urinary incontinence, this technique is responsible for pelvic neuromuscular activation through electrical impulses, causing frequent contraction of muscle fibers for strengthening and re-education in this pathology. the objective of this research was to analyze bibliographic information where articles with scientific evidence from different authors on neuromuscular electrical stimulation were selected, intended for patients suffering from pelvic floor dysfunctions due to urinary incontinence. the present work is of a bibliographic documentary type, which deals with the effects of neuromuscular electrical stimulation in patients with urinary incontinence, for which a compilation of scientific databases was carried out such as: pubmed, scielo, elsevier, sage journals, springer link, therapeutic advances in urology. the selection and evaluation of the scientific articles was carried out, thus recognizing the methodological quality with inclusion and exclusion criteria in the pedro scale, a total of 90 clinical trials were found, of which 35 articles were used with a score greater than or equal to 6. the search and analysis of scientific studies evidenced the efficacy of the therapeutic treatment of neuromuscular electrical stimulation of the posterior tibial nerve that benefits muscle strengthening, thus reducing symptoms with positive effects on functional recovery in patients with urinary incontinence, even reaching replace surgical intervention.